2-Dimensional Simulations of Pit Propagation and Multi-Pit Interactions. Issue 8 (1st August 2022) - Nguyen, Van Anh; Newman, Roger C.; Laycock, Nicholas J.
Abstract : This work presents a reaction-transport model for pit propagation coupled with a phase field method to model the moving boundary at the corroding surface. This enables numerical simulations of the simultaneous propagation of multiple pits in close proximity to each other to study the interactions between pits under galvanostatic conditions, with limited applied currents. Results show the formation of lacy covers over pits in stainless steel, which is due to undercutting of the surrounding surface, and reveal the development of other complex morphologies arising from the interaction between neighboring pits; e.g., the growth of "pits within pits" and the evolution of "champion pits." Such observations are due to the shrinkage of the total active surface to sustain the limited current as pits grow larger. The proposed model can be a valuable tool for studying the evolution of pit morphology in more realistic scenarios when multiple pit initiation sites are present.